Використання онтологій для підвищення якості пошуку інформації для поповнення баз знань інтелектуальних систем - Вороной, Олексій (Видавництво Національного університету «Львівська політехніка», 2009)
This work shows the concept of building muldagent system for search of knowledge in distributed unstructured sources of information. Contents, main functions of agents communication during solving task cf creating knowledge in intellectual system is proposed. To improve quality of knowledge search requests to seach systems are created according to known subject.
Keywords: multiagent system; distributed sources; intellectual system; багатоагентні системи; інтелектуальна система